2019
DOI: 10.4236/tel.2019.91004
|View full text |Cite
|
Sign up to set email alerts
|

Institutions and the Economic Performance of Central African Countries

Abstract: The purpose of this paper is to examine the combined effect of political and economic institutions on the economic performance of the countries of Central Africa. To do this, we use dynamic panel data over the period 1996-2013. Using Principal Component Analysis (PCA) to understand the multidimensionality of institutions through a composite indicator, and applying the estimation technique based on the Generalized Moment Method (GAM) to capture the impact of institutions on economic performance, we arrive at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Authors concluded that there was positive and statistically significant effect of financial development and institutional quality on economic growth for the concerned group of countries. Kane et al (2019) studied Central African countries for the impact of political and economic institutions on their economic performance for the period of 1996-2013. Authors concluded that institutions were hindering economic performance of Central Africa both individually and as group.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Authors concluded that there was positive and statistically significant effect of financial development and institutional quality on economic growth for the concerned group of countries. Kane et al (2019) studied Central African countries for the impact of political and economic institutions on their economic performance for the period of 1996-2013. Authors concluded that institutions were hindering economic performance of Central Africa both individually and as group.…”
Section: Literature Reviewmentioning
confidence: 99%